2022
DOI: 10.1136/bmjopen-2021-060436
|View full text |Cite
|
Sign up to set email alerts
|

Development of a core measurement set for research in degenerative cervical myelopathy: a study protocol (AO Spine RECODE-DCM CMS)

Abstract: IntroductionProgress in degenerative cervical myelopathy (DCM) is hindered by inconsistent measurement and reporting. This impedes data aggregation and outcome comparison across studies. This limitation can be reversed by developing a core measurement set (CMS) for DCM research. Previously, the AO Spine Research Objectives and Common Data Elements for DCM (AO Spine RECODE-DCM) defined ‘what’ should be measured in DCM: the next step of this initiative is to determine ‘how’ to measure these features. This protoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…The advent of a minimum dataset for DCM (AO Spine RECODE-DCM) should help circumvent this in the future, by ensuring key determinants of disease are recorded. 91 …”
Section: Discussionmentioning
confidence: 99%
“…The advent of a minimum dataset for DCM (AO Spine RECODE-DCM) should help circumvent this in the future, by ensuring key determinants of disease are recorded. 91 …”
Section: Discussionmentioning
confidence: 99%
“…This heterogeneity leads to publication bias, hampering interstudy comparison and guideline creation 15,16 . This has motivated recent interest in developing a core measurement set for DCM 9,17,18 and the recommendations to use a set of multiple subjective and objective measures 17 …”
Section: Discussionmentioning
confidence: 99%
“…This heterogeneity leads to publication bias, hampering interstudy comparison and guideline creation. 15,16 This has motivated recent interest in developing a core measurement set for DCM 9,17,18 and the recommendations to use a set of multiple subjective and objective measures. 17 The JOACMEQ questionnaire is the first DCM-specific questionnaire that attempts to jointly assess neurological function, disability, and QoL associated with.…”
Section: Discriminat Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…DNA damage-inducible transcript 4 (DDIT4), also called DNA damage response 1 (REDD1) and stresstriggered protein (RTP801), consists of 232 amino acids and is mainly found in the cytoplasm and nucleus [11,12]. Upon stress induction, including oxidative stress, endoplasmic reticulum stress, hypoxia and starvation [11,[13][14][15], DDIT4 inhibits mTOR signalling by stabilizing the tuberous sclerosis complex (TSC1-TSC2) [16,17], DDIT4 is aberrantly expressed at low levels in multiple tumours, including gastric cancer [18], breast cancer [19], glioma [20] and other tumours [21][22][23] The antisense transcript of DDIT4 encodes the lncRNA DDIT4-AS1, which has a length of 847 bp and consists of two exons. Numerous studies have indicated that abnormal expression of antisense lncRNAs contributes to tumorigenesis, oncogenic progression and the hallmarks of cancer [24].…”
Section: Introductionmentioning
confidence: 99%